(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2-1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 23:43:03
(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2-1(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2-1(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2
(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2-1
(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2-1
(1/x-1-1)/x平方+2x+1/x平方-1,其中x=根号2-1
原式=(1-x+1)/(x-1)÷(x+1)²/(x+1)(x-1)
=(2-x)/(x-1)÷(x+1)/(x-1)
=(2-x)/(x-1)*(x-1)/(x+1)
=(2-x)/(x+1)
=(2-√2+1)/(√2-1+1)
=(1-√2)/√2
=(√2-2)/2
x平方+x+1
x/x平方-x+2=2x/x+1
(x平方+x)(x平方+x-2)=-1 用换元法
x平方-3[2x-5(x平方-x+1)]
{x平方+x+1}{x平方+x+2}减12
2/x-x的平方-1/x的平方-x
(x+1)平方-2x
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
请化简:(x的平方-1)(x的平方-x)分之(x的平方+x)(x的平方-2x+1)
(2x+1)平方-x平方
X平方+1/X平方-1 -X-2/X-1 / X-2/X
x(x平方-1)+2X平方(X+1)-3X(2X-5)帮个忙
(x-1/x平方-6x+9)-(1/x-3)-(2x/9-x平方)
x(x的平方-2x+1)-3x(x的平方-4x+1)
(X+2)/(X的平方-2X)-(X-1)/(X的平方-4X+4) 化简
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
(x+1/x)的平方-3(x+1/x)+2
[(x+2)/(x+3)-(x+1)/(x+2)+(x+4)/(x+5)-(x+3)/(x+4)]/[(x的平方+7x+13)/(x的平方+8x+15)]